Respuesta :
We know what y equals already.
y = x + 5
2x - x + 5 = -2
x + 5 = -2
-5 -5
x = -7
y = -7 + 5
y = -2
Now we have our values
Answer: (-7,-2)
or
x = -7
y = -2
y = x + 5
2x - x + 5 = -2
x + 5 = -2
-5 -5
x = -7
y = -7 + 5
y = -2
Now we have our values
Answer: (-7,-2)
or
x = -7
y = -2
So, we substitute the y in the second equation to solve for x-value.
2x-(x+5) = -2
2x-x-5 = -2
x-5 = -2
+5 +5
x = 3
As we got the x-value, we now have to find the value of y.
y = x+5
y = 3+5
y = 8
So, the answer is (3,8)
HOPE THIS HELPS!!!!!
2x-(x+5) = -2
2x-x-5 = -2
x-5 = -2
+5 +5
x = 3
As we got the x-value, we now have to find the value of y.
y = x+5
y = 3+5
y = 8
So, the answer is (3,8)
HOPE THIS HELPS!!!!!